Image Steganography based on Fernet Symmetric Encryption and Odd-Even Pixel Modification (International Journal of Engineering and Computer Science, 2024)
The combination of steganography and cryptographic approaches for information concealing has piqued the curiosity of numerous researchers. We also integrate those two methods in our research. Using Fernet symmetric encryption and odd-even pixel alteration, this research presents a novel method for image steganography that distributes the data equally throughout the image. To create a stego image, the sender uses a password to encrypt a secret message embedded into an image's red channel. The stego image resembles the original cover image, while the underlying secret data is concealed from human view. The main goals of the system—encryption, consistent data concealing, and message retrieval—were all successfully met. Before integrating the secret data into the image, it can be easily and successfully secured using symmetric encryption using the Fernet cipher. By adding another layer of security to the system, the password feature makes it harder for unauthorized users to access hidden data. By altering image pixels according to whether they are odd or even, the odd-even pixel modification-based steganography approach makes it possible to conceal data. Based on the experiment's results, it can be concluded that this approach embeds concise messages with a high visual quality.